Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T20:12:14+01:00
A) y=2t-3x
-3x=y-2t
x=-(y-2t)/3
x=

b)y=2(x-1)
y=2x-2
2x=y+2
x=(y+2)/2
x=y/2+1

c)y=2/x-1
2/x=y+1
1/x=(y+1)/2
x=2/(y+1)

d)p=1/3(a²+2ax)
p=1/3a²+2/3ax
2/3ax=p-1/3a²
x=(p-1/3a²)/2/3a
x=(p-1/3a²)*3/2a
x=3p/2a-1/2a³
1 5 1
2010-03-04T20:16:13+01:00
A)
y=2t-3x /:2t
y/2t= -3x /:(-3)
x= y/(-3)2t
B)
y=2(x-1)
y=2x-2 /+2
2+y=2x /:2
2+y/2=x
C)
y=2/x-1 /+1
y+1=2/x /:2
y+1/2=x


  • tkzs
  • Rozwiązujący
2010-03-04T20:21:01+01:00
A)
y = 2t - 3x / :2t
y / 2t = -3x / :(-3)
x = y / (-3)2t
b)
y = 2(x - 1)
y = 2x - 2 /+2
2 + y = 2x /:2
2 + y / 2 = x
c)
y = 2 / x - 1 /+1
y + 1 = 2 / x /:2
y + 1 / 2 = x